Level of involvement of four selected cytochrome P450s (CYPs) in pyrethroid-resistant Anopheles gambiae (s.s.) and Anopheles coluzzii across Côte d’Ivoire - Joseph Chabi; Constant V.A. Edi; Bernard L. Kouassi; Constant N.G. Gbalegba; Armand E. Kouassi; Jackson K.I. Kouame; Yves K.A. Kadio; Firmain N. Yokoly; Louise B. Golou; Janice Gouaméné; Jean-Baptiste Assamoi; Emmanuel Tia; et al. (Current Research in Parasitology and Vector-Borne Diseases)
In Côte d'Ivoire, there is a high intensity of pyrethroid resistance in malaria vectors which may threaten successful vector control. Molecular studies of the target site mutation in the voltage-gated sodium channel (VGSC) 1014F show that the gene frequencies of these mutations are high, widely spread across Côte d’Ivoire, and even fixed in some areas. To further characterize insecticide resistance in Côte d’Ivoire beyond target site mutations, the metabolic resistance mechanism was explored. Overexpression of the metabolic enzyme cytochrome CYP6M2, CYP6P3, CYP6P4, and CYP6P5 was investigated in Anopheles gambiae (s.s.) and An. coluzzii collected from 30 insecticide resistance monitoring sites across the country in 2021 and 2022. Quantitative real-time polymerase chain reaction (qRT-PCR) assay was carried out using RNA-later preserved 60 surviving mosquitoes from each site after phenotypic susceptibility tests. Additionally, a subsample of about 100 mosquitoes from each site was identified to species by PCR, and the frequency of the VGSC 1014F and 1014S was determined. All four CYPs were found to be overexpressed in Côte d’Ivoire with at least one CYP statistically significantly overexpressed in 27 of the 30 sites investigated compared to the susceptible An. gambiae (s.s.) Kisumu (P < 0.005). CYP6M2 was overexpressed in 89% of sites and was the sole overexpressed gene in 10 sites, while the overexpression of CYP6P3 was found in only 10 sites. CYP6P4 and CYP6P5 were overexpressed in 16 and 13 sites, respectively. Furthermore, seven sites (Adzopé, Bongouanou, Daloa, Gagnoa, Guiglo Jacqueville, and Sassandra) had overexpression of all four CYPs. Overall, An. coluzzii showed higher overexpression of CYPs than An. gambiae (s.s.). This study highlights the involvement of selected CYPs in insecticide resistance where target site mutation genes are already present, suggesting that insecticide resistance is complex and multifaceted at a molecular level. Where feasible, it may be helpful to include metabolic resistance surveillance to further characterize insecticide resistance.